Measurement of thermophoretic parameters for binary gas mixtures - Razali, Mohd Azahari; Mori, Masayuki; Suzuki, Masataro; Masuda, Wataru (Elsevier, 2013)
The thermophoretic velocity of a particle in a gas mixture is measured by means of a microgravity experiment. Adopted particles are PMMA spheres of 2.91 mm in mean diameter, and gas mixtures chosen are argon–nitrogen, argon–carbon dioxide, and nitrogen–carbon dioxide. The temperature gradient and the pressure are 60 K/mm and 70 kPa, respectively. Terminal velocities of particles suspended in a gas are individually measured. The tangential momentum accommodation coefficient is estimated from experimental result by assuming the thermal accommodation coefficient at unity, and it is compared with predictions calculated from values of composing pure gases by means of some methods given in references; among those methods, the intermolecular-interactionbased method is found to be the best for all mixture conditions.